Geometric sequence based multipath routing protocol for multi-hop ad hoc networks. Issue 4 (7th November 2016) - Tashtoush, Yahya M.; Alsmirat, Mohammad A.; Alghadi, Tasneem
Abstract : Purpose: The purpose of this paper is to propose, a new multi-path routing protocol that distributes packets over the available paths between a sender and a receiver in a multi-hop ad hoc network. We call this protocol Geometric Sequence Based Multipath Routing Protocol (GMRP). Design/methodology/approach: GMRP distributes packets according to the geometric sequence. GMRP is evaluated using GloMoSim simulator. The authors use packet delivery ratio and end-to-end delay as the comparison performance metrics. They also vary many network configuration parameters such as number of nodes, transmission rate, mobility speed and network area. Findings: The simulation results show that GMRP reduces the average end-to-end delay by up to 49 per cent and increases the delivery ratio by up to 8 per cent. Originality/value: This study is the first to propose to use of geometric sequence in the multipath routing approach.